2019
DOI: 10.1055/s-0039-1677763
|View full text |Cite
|
Sign up to set email alerts
|

Speech Sound Disorder and Visual Biofeedback Intervention: A Preliminary Investigation of Treatment Intensity

Abstract: A growing body of research suggests that cases of speech sound errors that have not responded to previous intervention can sometimes be eliminated through speech therapy incorporating visual biofeedback. Aside from considerations related to the specific biofeedback type, acquisition and generalization of a motor plan may be linked to treatment intensity. Several researchers have raised the possibility that inadequate dosage levels may present a significant barrier to success. Thus, the current study aimed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Perhaps the intervention dosage or intensity was inadequate. Hitchcock et al (2019) found a significant positive relationship between U-VBF treatment intensity and outcomes, and it is, therefore, possible that the once-per-week treatment these children received was insufficient to completely remediate the disorder. Unfortunately, long-term follow-up was not available for these children.…”
Section: Discussionmentioning
confidence: 97%
“…Perhaps the intervention dosage or intensity was inadequate. Hitchcock et al (2019) found a significant positive relationship between U-VBF treatment intensity and outcomes, and it is, therefore, possible that the once-per-week treatment these children received was insufficient to completely remediate the disorder. Unfortunately, long-term follow-up was not available for these children.…”
Section: Discussionmentioning
confidence: 97%
“…It has been proposed that increasing the intensity of practice sessions, for example, condensing a larger number of trials and sessions into a shorter duration of time, with fewer opportunities to reestablish the old motor pattern between correct trials, might be facilitative of generalization learning (Preston, Leece, & Maas, 2016). Controlled studies comparing an equal dose of intervention delivered on an intensive schedule, in contrast with the distributed schedule of this study, will be essential to test this hypothesis (Hitchcock et al, 2019).…”
Section: Differing Individual Profiles Of Generalization Learningmentioning
confidence: 95%
“…For Jenna, blinded listeners' ratings of maintenance probes showed robust gains for vocalic variants, but for consonantal /ɹ/, which began with a high level of accuracy, there was a decrease in accuracy to slightly below baseline levels. 3 While no conclusive interpretation can be attached to these findings, they raise the possibility that the higher cumulative dose of practice completed by Clara was more conducive to longterm generalization than the lower dose delivered to Jenna (Hitchcock et al, 2019). Thus, the criteria for discontinuing intervention might need to be made more stringent in future implementations of challenge point practice.…”
Section: Differing Individual Profiles Of Generalization Learningmentioning
confidence: 99%
“…Aims and role of speech and language therapy, grouped according to (1) for which US has been selected by SLT clinicians.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In the Speech and Language Therapy (SLT) profession, there is growing evidence to support its application as a tool for the assessment and treatment of speech and swallowing disorders. [1][2][3][4] There are fundamental constraints to integration of US into SLT clinical practice such as cost, availability of equipment and lack of focused training. 2,5 There is, however, a drive among the profession to start adopting US into practice while research to establish reliability of data acquisition and interpretation continues.…”
Section: Introductionmentioning
confidence: 99%